Bamboo construction as a sustainable building technology from a structural and materials engineering perspective - Ross, Sheila (Department of Civil Engineering, 2021)
The objective of this dissertation is to determine whether bamboo culms or stems are suitable for use as a construction material for permanent structures, from an engineering as well as a sustainability perspective. A secondary objective is to establish whether this would be a suitable building technology for South Africa. The research is desk-top in nature and involves reviewing articles in online journals and publications and collating the information into a coherent form. Eleven species of bamboo commonly used in construction worldwide are selected for investigation of their material and engineering properties. Based on the variations found in the various species of bamboo, approaches to engineering modelling and design of bamboo structures are detailed and discussed. Furthermore, four case studies are presented that illustrate the various areas where bamboo construction is currently used. Finally, research is done regarding the level of the South African bamboo industry, including whether a bamboo species currently exists in South Africa that would be suitable for construction purposes. The preliminary literature review indicated that there is a lack of scientific or structural information regarding bamboo as a building material from an engineering or materials perspective, both globally as well as in South Africa. Although a substantial amount of information was subsequently found on the various aspects of bamboo as a structural material, the information varies widely between sources, which is ascribed to variations in test methods as well as to the location of the species being tested. The design codes and standards from various countries for bamboo design and construction are briefly reviewed. For countries where there is currently no bamboo design code or standard, such as South Africa, it is recommended that the International Standard, ISO 22156, be used as a design basis, using specific material properties relevant to the local species. Many publications state that bamboo is a sustainable building material, comparing favourably with other building materials. However, quantitative proof was found to be either lacking or unclear. Different methods were used in the publications to evaluate bamboo from an environmental perspective, making it difficult to compare and evaluate the different reports and results. However, despite the different methods, it appears that bamboo can be regarded as an environmentally favourable material, provided that local species are used in construction. The four case studies presented demonstrate that bamboo culms are suitable for use in large structures, such as bridges or trusses, as well as for smaller structures such as buildings or houses. They also illustrate the issues that can occur if the design intent is not understood or correctly carried out during construction. South Africa has one bamboo species considered suitable for construction, namely Bambusa balcooa, which is grown in various parts of the country. The properties of the South African plants have not been established as yet. However, theoretical engineering and material properties as determined elsewhere in the world indicate that this is a viable construction material. Further areas of research are the establishment of the material and engineering properties of the local South African bamboo species Bambusa balcooa, as well as further research into the behaviour of bamboo in fire conditions.